The future we need organizing for a better democracy in the twenty-first century - Smiley, Erica; Gupta, Sarita (Political activist) (Book collections on Project MUSE., 2022)
In The Future We Need, Erica Smiley and Sarita Gupta bring a novel perspective to building worker power and what labor organizing could look like in the future, suggesting ways to evolve collective bargaining to match the needs of modern people--not only changing their wages and working conditions, but being able to govern over more aspects of their lives. Weaving together stories of real working people, Smiley and Gupta position the struggle to build collective bargaining power as a central element in the effort to build a healthy democracy and explore both existing levers of power and new ones we must build for workers to have the ability to negotiate in today and tomorrow's contexts. The Future We Need illustrates the necessity of centralizing the fight against white supremacy and gender discrimination, while offering paths forward to harness the power of collective bargaining in every area for a new era--